The Phenomenon of Vulnerable Population Exploitation Going Viral on Social Media: A Social Construction of Impression Management Among Content Creators - Chriestine Lucia Mamuaya; Mohammad Suud; Heru Dwi Herbowo; Yudi Harianto Cipta Utama; Sugeng Pujileksono; Meyer Eunike Nander; Blandina Suprianata Dewi (International Journal of Education, Vocational and Social Science, 2026)
This study examines the growing phenomenon of vulnerable population exploitation on social media platforms—including TikTok, YouTube, Instagram, and Facebook—in which content creators publish videos featuring elderly individuals, persons with disabilities, children, and impoverished groups to generate digital revenue and audience engagement. Grounded in Peter L. Berger and Thomas Luckmann's theory of Social Construction of Reality and Erving Goffman's Impression Management framework, this research investigates the motivational factors driving content creators to produce such content and the social constructions these creators disseminate through digital platforms. Employing a qualitative approach through literature review and content analysis, the study draws on multiple academic journals, relevant legislation, and publicly accessible social media content. The findings reveal that economic incentive, social recognition, and algorithmic reinforcement are the primary drivers of viral exploitation content. Content creators strategically perform emotional staging—framing scenes of poverty, disability, and suffering—to elicit empathy from audiences and convert it into digital coins, views, and subscribers. This practice constructs a distorted social reality in which vulnerability is commodified and suffering becomes a form of entertainment. The study recommends enhanced multi-stakeholder collaboration among the Ministry of Communication and Information (Kominfo), Ministry of Social Affairs (Kemensos), and Regional Social Services (Dinsos) to regulate exploitative content, alongside greater platform accountability and improved digital literacy among the public.